Processing focus in Turkish and English :|a study on monolingual and bilingual language processing - Kurt, Didem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
This study investigated how focus (broad and narrow) was processed in Turkish as a first language (L1) and English as a second language (L2). Two sentence completion tasks (Experiment 1 in Turkish, Experiment 3 in English) and two eye-tracking experiments (Experiment 2 in Turkish, Experiment 4 in English) were conducted to examine whether or not readers assign broad focus to the constituent receiving sentential stress and whether or not changes to word-order are taken as cues to mark narrow focus. The sentence completion data showed that, in sentences with ditransitive verbs, the immediately preverbal object in L1 Turkish and the rightmost object in L1 and L2 English received focus. The results of the eye-tracking experiments further supported this. Experiment 2 also showed that Turkish speakers were sensitive to word-order cues for broad/narrow focus; and processing and revision of the narrowly-focused constituent was costlier, which is attributed to its deeper encoding in memory. The results for Experiment 4 indicated that although Turkish L2 learners assigned sentential stress to the rightmost object, they were not sensitive to the word-order cues for broad and narrow focus. This could be due to the limited input for scrambling in the L2. Alternatively, the L2 learners could be unable to process information at the syntax-discourse interface which requires integration of syntactic (word-order) and discourse-level (given-before-new) information (Sorace & Filiaci, 2006).
Keywords: Intercultural communication.; Interlanguage (Language learning); Second language acquisition.